DEMOGRAPHIC CHARACTERISTICS OF THE REPUBLIC OF BURYATIA - L. F. Pisareva; N. P. Lyakhova; I. N. Odintsova; D. A. Perinov; Т. N. Chemitdorzhieva; Ye. A. Shukhoeva (Бюллетень сибирской медицины, 2015)
From 1989 to 2013, demographic processes in the Republic of Buryatia were analyzed. Changes in the basic parameters of the population movement: births, deaths and migration were influenced by the sex and age structure of the population. The proportion of the Russians decreased from 69.9% in 1989 to 64.9% in 2010 and the number of the Buryats increased from 24.0 to 29.5%. With the increase in the proportion of residents over 60 years, a process of the aging of the population was observed. In 2000–2013, there was a positive dynamics of the natural movement of the population, the natural increase in /Т ёь9013 was 5,8 per 1000 persons. Migration population decline in the Republic of Buryatia keeps stable.